Anthropometric, physical and cardiorespiratory fitness of 10-16 years children - Indranil Manna; Swadesh Ranjan Pan; Mohua Chowdhury (Al Ameen Medical College, 2014)
Objectives: The present study was undertaken to investigate the anthropometric, physical and cardiorespiratiory fitness of 10-16 yrs children. Background: Talent identification in sports is importance because they represent the achievement level of a particular group in future. There are very limited studies available in Indian context on talent identification in sports. Method: A total of 150 male children of 10-16 yrs age volunteered for this study; were divided equally into 3 groups (i) Prepubertal (age-11.0 ± 0.8yrs, n=50); (ii) Pubertal (age 13.5 ± 0.5 yrs, n=50); (iii) Postpubertal (age 15.5 ± 0.5 yrs, n=50). Selected anthropometric, physical and cardiorespiratiory fitness variables were measured for each group. Result: A significantly (P<0.05) greater height, body mass, BSA, LBM, mid upper arm circumference, hip and trunk flexibility, grip strengths, abdominal strength, elastic leg strength, maximum speed, peak power, VO2max, peak expiratory flow rate and blood pressure were observed in Postpubertal children when compared to Prepubertal and Pubertal children. However, a significantly (P<0.05) lower percent body fat, reaction time, maximal heart rate and recovery heart rates were noted in Postpubertal children when compared to Prepubertal and Pubertal children. The waist- hip ratio of pubertal children was noted significantly higher (P<0.05) when compared to prepubertal and postpurbertal children. No significant change was reported in BMI and resting heart rate among the groups. Conclusion: Identification of children at early stage of their growth and development may produce elite athletes in the future. Talent identification also can be used as a counseling technique that helps to discover and explore areas of talent for particular athletes.